New morphology data and geographic distribution expansion of Leposternon mineiro Ribeiro, Silveira & Santos-Jr, 2018 (Squamata, Amphisbaenia, Amphisbaenidae) - Pimenta Eleutério, Jady (2023)
We provide new morphological and geographic distribution data for Leposternon mineiro. Fifteen specimens of L. mineiro were analyzed (six specimens of the type series and nine additional specimens), in addition to 404 specimens of other species of the genus, used for identification and comparison. Meristic characters, morphometrics, head scale patterns and dentition matched the previously published diagnosis of the species, but we also found some variations compared to the type series. We expanded the ranges of the following diagnostic characters of L. mineiro: snout-vent length 221–380 mm, tail length 11.5–23.4 mm, 252–300 dorsal postpectoral halfannuli, 252–280 ventral postpectoral half-annuli, 14–16 caudal annuli, 26–37 dorsal segments and 24–39 ventral segments in a midbody annuli, and 2–4 precloacal pores. The new record from the municipality of Cristalina, State of Goiás, extends the geographic distribution of the species by 148 km west of nearest record.